A new species of Leptomenes Giordani Soika from Uganda (Hymenoptera: Vespidae: Eumeninae) - Selis, Marco (Zootaxa, 2020)
Leptomenes Giordani Soika, 1939 is an Afrotropical genus of small-sized potter wasps, presently comprising eight species in continental Africa and another three species in Madagascar. The continental species are mainly distributed in eastern Central Africa, but some species reach Kwazulu-Natal in the south and Senegal in the west (Carpenter et al. 2010).